2016
DOI: 10.1590/1678-4324-2016160586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic fertilizers on the growth and yield of bush bean, winged bean and yard long bean

Abstract: VC (20%), TC (20%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
10
15
0
Order By: Relevance
“…This result is in agreement with previous result by [3] who stated that the number of pods produced by haricot bean increased with increase in lime. It was also reported that organic manure increased the number of pods in bush bean, winged bean and long bean [31]. It also agrees with the report of improved pod number of cowpea following treatment with organic manure [32].…”
Section: Discussionsupporting
confidence: 85%
“…This result is in agreement with previous result by [3] who stated that the number of pods produced by haricot bean increased with increase in lime. It was also reported that organic manure increased the number of pods in bush bean, winged bean and long bean [31]. It also agrees with the report of improved pod number of cowpea following treatment with organic manure [32].…”
Section: Discussionsupporting
confidence: 85%
“…Experiment conducted pot greenhouse in Rubona-reserch site in Rwanda to identify as superior genotypes and nodulation of both bush and climbing bean genotypes under acidic, low phosphorus soils, results showed that highest score was 22.9g/pot for climbing bean which agreed with this study (Gatesi and Nsanzimana, 2017). Islam, et al, (2016) did a study on yield response of three beans, bush, winged and long genotypes under organic fertilizers growing conditions, they found significant variation in yield whereby some genotypes produced as high as 2980kg/ha, which agree to the current result. Also, Singh et al, (2013) observed the high yield genotypes with tolerance to sodic soils were the best genotypes selected by farmers in rice experiment in India, which supports also this experiment.…”
Section: Discussionsupporting
confidence: 86%
“…The water content could have been lost in evaporation and transpiration processes leading to also equal loss of water content in the bush bean shot system during drying process. The results are also in agreement with Islam et al (2016) who recorded that vermin compost was found to be not significantly different from control in increasing mean dry biomass plant height of yard long beans. A contrasting finding confirmed nonsignificant effect on plant height as a result of spray of varied concentration of panchagavya foliar application on green gram (Somasundaram et al, 2003).…”
Section: Effect Of Selected Commercial Organic Fertilizers and Local supporting
confidence: 92%
“…This may be attributed to its nutrient composition especially nitrogen and its ability to release nutrients into the soil for plant uptake that consequently facilitated plant growth. Relatedly Islam et al (2016) reported that vermicompost significantly increased the plant height of long and bush beans. Similar results were reported by Singh and Chauhan (2009) in bush beans.…”
Section: Effect Of Selected Organic Fertilizers and Local Manure On Tmentioning
confidence: 95%